2008
DOI: 10.2202/1548-923x.1366
|View full text |Cite
|
Sign up to set email alerts
|

"Failure to Assign Failing Grades": Issues with Grading the Unsafe Student

Abstract: In a grounded theory study examining the process of precepting an unsafe student, it was found that preceptors assigned passing grades to students who in fact should not have passed. Although preceptors perceived their role as gatekeepers for the profession, by not assigning failing grades to students who should not have passed a course, essentially they were abdicating their responsibility. Indeed, the simple act of assuming responsibility for precepting a student implies professional as well as pedagogical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(150 citation statements)
references
References 24 publications
7
119
0
24
Order By: Relevance
“…[28] Preceptors themselves have stressed the need for clearer role expectations, guidance, and support; [17,29] however, preceptors have reported that they feel ill-prepared to assume the role. [13,30,31] Kowalski et al [15] suggest that a lack of preparation is a reason for burnout and dissatisfaction with nurses working as preceptors. There is consensus in the literature that preceptors need some type of preparation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Preceptors themselves have stressed the need for clearer role expectations, guidance, and support; [17,29] however, preceptors have reported that they feel ill-prepared to assume the role. [13,30,31] Kowalski et al [15] suggest that a lack of preparation is a reason for burnout and dissatisfaction with nurses working as preceptors. There is consensus in the literature that preceptors need some type of preparation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[27] This sense of accountability and responsibility is viewed by preceptors as critical, especially if students are deemed unsafe or incompetent. [29][30][31] Preceptors report less satisfaction in the role when students are perceived as "difficult". [44] Research indicates that poorly performing students are often a significant source of stress, leading to feelings of self-doubt, fear, anxiety, anger, and frustration for preceptors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The issue of reluctance to fail unsafe or incompetent students has been documented by a number of scholars in nursing. [10,12,20] For example, faculty advisors who lack knowledge, experience or confidence in the evaluation role are reluctant to fail unsafe or marginal students. [9,12,14,20] In addition, few schools of nursing have written policies or guidelines for faculty advisors to follow when dealing with unsafe students.…”
Section: Faculty Advisor Role and Responsibilities In Preceptorshipmentioning
confidence: 99%
“…Identification and intervention are critical processes in working with and managing students who are unsafe or whose clinical performance is marginal or failing to meet the program objectives. [10][11][12] Many faculty advisors, however, may have difficulty in identifying students with unsafe practices and particularly in making appropriate decisions regarding unsafe performance. [11,13,14] Multiple interpretations of what constitutes 'unsafe practice' and the absence of guidelines for response reflect the complexity of the issue.…”
Section: Introductionmentioning
confidence: 99%